Translation Methods for Culture-Loaded Words In The "Jiu Ge" of The Chu Ci - Sun, Hexin; Tian, Chuanmao (Classical Literature, 2025)
This study investigates the translation strategies Arthur Waley employed for culture-loaded words in the "Jiu ge" (The Nine Songs) section of the Chu Ci, with Susan Bassnett’s cultural translation theory (centered on cultural functional equivalence and cultural symbol transfer) as the primary analytical framework, integrated with Eugene Nida’s cultural taxonomy. As the origin of Chinese romantic literature, the Chu Ci holds profound literary and cultural value; advancing its English translation is practically significant for promoting China’s fine traditional culture and deepening Sino-Western cultural exchanges. However, research on the English translation of "Jiu ge" within the Chu Ci remains scarce. Thus, this study focuses on culture-loaded words in Waley’s translation of the "Jiu ge" , analyzing the methods he used to handle such words, aiming to provide references for future translators. Findings reveal that the "Jiu ge" embodies abundant Chinese-specific cultural connotations in social customs, religious shamanism, astronomy, and geography. This study identifies nine translation methods employed by Waley: image substitution, generalization plus annotation, explicitation, concretization, free translation, free translation plus amplification, literal translation plus adaptation, transliteration plus amplification, and use of similar onomatopoeia. These methods offer implications for translating cultural expressions in Chinese classics—particularly texts with regional and ritualistic connotations like the "Jiu ge"—rather than being universally applicable to all classical Chinese works.